2005
DOI: 10.1091/mbc.e05-06-0536
|View full text |Cite
|
Sign up to set email alerts
|

SUMO-1 Modification Alters ADAR1 Editing Activity

Abstract: We identify ADAR1, an RNA-editing enzyme with transient nucleolar localization, as a novel substrate for sumoylation. We show that ADAR1 colocalizes with SUMO-1 in a subnucleolar region that is distinct from the fibrillar center, the dense fibrillar component, and the granular component. Our results further show that human ADAR1 is modified by SUMO-1 on lysine residue 418. An arginine substitution of K418 abolishes SUMO-1 conjugation and although it does not interfere with ADAR1 proper localization, it stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
93
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(98 citation statements)
references
References 72 publications
(113 reference statements)
5
93
0
Order By: Relevance
“…Likewise, proteomic approaches revealed that RNA-binding proteins are the predominant group among small Ubiquitin-like modifier (SUMO) conjugation substrates, including several hnRNPs, SR family members and spliceosome components (50,51). Furthermore, SUMO conjugation has been found to regulate different aspects of mRNA metabolism such as pre-mRNA 3 0 end processing and RNA editing, by modifying the function of poly(A) polymerase, symplekin and CPSF-73 in the former case and ADAR1 in the latter (52,53). It would be interesting to elucidate whether Ub or Ubl conjugation, in particular SUMO, could affect SR protein activities.…”
Section: Post-translational Modifications Of Sr Proteins: Above and Bmentioning
confidence: 99%
“…Likewise, proteomic approaches revealed that RNA-binding proteins are the predominant group among small Ubiquitin-like modifier (SUMO) conjugation substrates, including several hnRNPs, SR family members and spliceosome components (50,51). Furthermore, SUMO conjugation has been found to regulate different aspects of mRNA metabolism such as pre-mRNA 3 0 end processing and RNA editing, by modifying the function of poly(A) polymerase, symplekin and CPSF-73 in the former case and ADAR1 in the latter (52,53). It would be interesting to elucidate whether Ub or Ubl conjugation, in particular SUMO, could affect SR protein activities.…”
Section: Post-translational Modifications Of Sr Proteins: Above and Bmentioning
confidence: 99%
“…An effect of sumoylation on the activity of different RNAbinding proteins has been reported (57,60,61), and sumoylation has been shown to regulate mRNA 3′-end processing (61,62). SUMO modification of nucleolar proteins controls their subnuclear distribution and members of the SENP family are concentrated within the nucleolus.…”
Section: Sf2/asf Interacts With Ubc9 and Stimulates Sumoylation Of Spmentioning
confidence: 99%
“…To confirm that the signals obtained were not simply due to random associations between overexpressed proteins located in a small compartment, we used a nucleolar protein, nucleolin, which is not expected to interact with the ADARs. Electron and fluorescence microscopy have suggested that nucleolin localizes in the dense fibrillar and granular components of the nucleoli (Biggiogera et al 1990), while ADAR2 localizes to the periphery of the dense fibrillar component (Desterro et al 2003(Desterro et al , 2005. With quantitative confocal microscopy, we observe at least significant colocalization of ADAR2 and nucleolin within the nucleoli (data not shown), and when BRET 2 signals were measured between Rluc-ADAR2 and GFP 2 fused to nucleolin, the signal also increased with increased GFP 2 : Rluc ratio (Fig.…”
Section: Adar2 Exists As Dimers In Living Mammalian Cellsmentioning
confidence: 99%